2011
DOI: 10.15177/seefor.11-09
|View full text |Cite
|
Sign up to set email alerts
|

Digital Photogrammetry – State of the Art and Potential for Application in Forest Management in Croatia

Abstract: Background and purpose: The main goal of this paper is to inform forestry community about the latest developments in digital photogrammetry, as well as to present its possible application in forest management. For this purpose, the current state of technological development of the main tools of digital photogrammetry (digital aerophotogrammetric cameras and digital photogrammetric workstations) has been presented. Furthermore, two adjusted methods of manual digital photogrammetry for application in forest mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Currently, both methods (digital stereo-photogrammetry and ALS) are suitable and enable estimation of H and CD at tree level [6,32]. Research on applicability of high-spatial resolution stereo-images [33][34][35][36] or high-density ALS data [14,37,38] for H estimation showed that H could be estimated with both methods with high accuracy and with no statistically significant difference compared to field measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, both methods (digital stereo-photogrammetry and ALS) are suitable and enable estimation of H and CD at tree level [6,32]. Research on applicability of high-spatial resolution stereo-images [33][34][35][36] or high-density ALS data [14,37,38] for H estimation showed that H could be estimated with both methods with high accuracy and with no statistically significant difference compared to field measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The stereoscopic view was produced by using the stereo-viewing DPW system (NVIDIA GeForce 9800 GT graphic card, Hyundai IT W220S stereo-monitor and Hyundai polarised interlaced stereo-glasses). A detailed description of the equipment and photogrammetric measurement methods is provided by Balenović et al (2011).…”
Section: Photogrammetric Datamentioning
confidence: 99%
“…In SEE countries the application of remote sensing in practical forestry usually implies only the use of orthophoto maps to assist in field orientation, although there are studies dealing with the potential use of satellite images [100], as well as digital aerial images [101][102][103] in forest management. But, unlike satellite and aerial images, the ALS technology has not yet been a subject of research in Croatia, as well as the entire region with the exception of Slovenia [12][13][14].…”
Section: Conclusion and Future Research Streamsmentioning
confidence: 99%